Dynamic Modelling and Hybrid Non-Linear Model Predictive Control of Induced Draft Cooling Towers With Parallel Heat Exchangers, Pumps and Cooling Water Network - Craig, Ian K. (University of Pretoria, 2019)
Thesis (PhD)--University of Pretoria, 2019.